Directly ageing the Caribbean spiny lobster, Panulirus argus with validated band counts from gastric mill ossicles. (30th November 2018) - Gnanalingam, Gaya; Butler, Mark J; Matthews, Thomas R; Hutchinson, Emily; Kilada, Raouf
Abstract: In crustaceans, ecdysis was long believed to result in the loss and replacement of all calcified structures, precluding the use of conventional ageing methods. However, the discovery of bands in the gastric ossicles of several crustaceans with some correlation with age suggests that direct age estimation may be possible. We applied this method to a tropical spiny lobster, Panulirus argus, one of the most iconic and economically valuable species in the Caribbean. The presence of growth bands was investigated using wild lobsters of unknown age and was validated with captive reared lobsters of known age (1.5–10 years) from the Florida Keys, Florida (USA). Bands were consistently identified in ptero- and zygo-cardiac ossicles of the gastric mill and did not appear to be associated with moulting. Validation with known age animals confirms that bands form annually. Counts between independent readers were reproducible with coefficients of variation ranging from 11% to 26% depending on reader experience and the structure used. This study demonstrates, for the first time, that direct age determination of P. argus is possible.